Look and Find, Fairy Tales: Snow White, Goldilocks, Little Mermaid, Sleeping Beauty, Three Little Pigs and More! - Tiritilli, Jerry (Lincolnwood, Ill. : Publications International, 1992)
Readers are asked to search for characters and items from famous legends.
Keywords: Picture puzzles -- Juvenile literature; Animals; Pictorial works; Juvenile literature; Fiction; Illustrated works